Optimal dose reduction of FOLFIRINOX for preserving tumour response in advanced pancreatic cancer: Using cumulative relative dose intensity. (May 2017) - Lee, Jong-chan; Kim, Jin Won; Ahn, Soyeon; Kim, Hyoung Woo; Lee, Jongchan; Kim, Young Hoon; Paik, Kyu-hyun; Kim, Jaihwan; Hwang, Jin-Hyeok
Abstract: Background: FOLFIRINOX has increased efficacy but also toxicity. Despite various modified FOLFIRINOX regimens, how much reduction is acceptable remains unclear. This study aimed to find the optimal relative dose intensity (RDI, %) of FOLFIRINOX that preserves tumour responses in patients with advanced pancreatic cancer (PC). Methods: We reviewed 201 patients with PC treated with first-line FOLFIRINOX during 2012–2015. We established a modified Hryniuk model (http://www.rdicalc.com ) and defined cumulative RDI (cRDI, %). The optimal cRDI thresholds for response rate (RR) and disease control rate (DCR) were assessed using receiver operating characteristic (ROC) analysis. Relationships between cRDI and haematologic toxicities (neutropenia and febrile neutropenia [FN]) were also analysed according to use of granulocyte colony-stimulating factor (G-CSF). Results: Among 156 eligible patients, 133 (48 locally advanced PC and 85 metastatic PC) completed initial treatment plan prior to the first radiological evaluation (median 58 days; 71.8% cRDI). For optimal cRDI thresholds, ROC curves showed a 71.2% cRDI for RR (83.3% sensitivity, 64.7% specificity, and 0.746 area under the curve [AUC]) and a 55.3% cRDI for DCR (93.6% sensitivity, 62.5% specificity and 0.805 AUC). Among 96 patients who did not receive prophylactic G-CSF, cRDI ≥80.1% was a significant predictor for frequent FN (73.7% sensitivity, 72.7% specificity and 0.793 AUC). There was no correlation between cRDI and haematologic toxicities in patients receiving prophylactic G-CSF. Conclusion: To preserve optimal RR and DCR in advanced PC, cRDI values for FOLFIRINOX >70% and >55%, respectively, are recommended. If cRDI is >80%, primary G-CSF prophylaxis is needed. Highlights: We established a modified Hryniuk model and defined cumulative relative dose intensity (cRDI, %). We assessed cRDI thresholds for response rate (RR) and disease control rate (DCR). A cRDI for FOLFIRINOX >70% is recommended to preserve RR. A cRDI for FOLFIRINOX >55% is recommended to preserve DCR. If cRDI for FOLFIRINOX is >80%, primary granulocyte colony-stimulating factor prophylaxis is needed.